Digital Marketing, The Effective Solutions For Marketing Shredded Tuna Products From Fishermen Villages At South Of Malang - Susilo, Trisno; Nugrahendi, Doni (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Indonesia possesses an extensive coastline and abundant marine resources, resulting in high demand for fishery products in both domestic and international markets. However, a significant portion of foreign demand remains unmet, indicating substantial opportunities for expansion. Beyond fresh and frozen fish, value-added processed seafood products offer advantages in terms of convenience, storage, durability, and distribution, while also contributing to the economic welfare of fishermen and their families. These products range from large-scale factory outputs, such as canned fish, to small-scale home industries and MSMEs producing items like shredded tuna. Effective marketing is a critical determinant of success for processed seafood products. In the context of digital transformation, social media platforms—including Facebook, Instagram, TikTok, YouTube, and WhatsApp—provide cost-effective and rapid channels for product promotion and market expansion. This study focuses on shredded tuna produced by home industries in the fishing village of Sendang Biru, South Malang. Although the product has been marketed through several online marketplaces, its reach and demand remain limited, both in terms of consumer awareness and sales volume. Therefore, a structured, comprehensive, and large-scale digital marketing strategy is required to enhance product visibility and demand. This research aims to improve the economic conditions and welfare of the Sendang Biru fishing community while serving as a pilot project for university students to generate income through content creation. Consistent, educational, and engaging content on Instagram and TikTok is expected to influence consumer purchasing behavior, where increased content intensity is directly associated with higher market demand.